THE EFFECT OF SURFACTANT ON PRE-MORDANTING AND pH OF DYEING PROCESS WITH NATURAL DYES - Atikah, Wulan Safrihatini; Muslim, Ikhwanul; Pratama, Sandi Mu'min (Jurnal Kimia Riset, 2023)
The dyeing process with natural dyes has disadvantages, including poor color fastness. A mordanting process is required to overcome these disadvantages. Conventional mordanting processes often use metal salts. This research will substitute the mordanting process using surfactants as mordant substances. The pH of the process influences the application of dyeing with natural dyes. This study aims to determine the effect of the pre-mordant process using surfactants and the pH of the dyeing process on the color characteristics of cotton and silk fabrics dyed with Cocos nucifera L dye extract. The surfactants used were cationic and non-ionic polymeric surfactants. This study was conducted in phases. The first phase involved the extraction of coconut fiber, and the second phase involved pre-mordanting the fiber with surfactants. The third stage is the dyeing process, which has variations in pH 3, 7, and 9. The evaluation results show that cationic surfactants have the potential to be used as a mordant and provide an increased anti-bacterial effect on processed fabrics. The optimal use of cationic surfactants was obtained using a concentration of 9 g/L and pH 7 for the cotton dyeing process. The optimum concentration was obtained at 9 g/L for the silk dyeing process, and the dyeing pH was 3.